ANALYSIS OF RELIABILITY OF NONRECTORABLE REDUNDANT POWER SYSTEMS TAKING INTO ACCOUNT COMMON FAILURES - V. A. Anischenko; A. N. Ivanova; E. L. Mislo (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Reliability Analysis of nonrestorable redundant power Systems of industrial plants and other consumers of electric energy was carried out. The main attention was paid to numbers failures influence, caused by failures of all elements of System due to one general reason. Noted the main possible reasons of common failures formation. Two main indicators of reliability of non-restorable systems are considered: average time of no-failure operation and mean probability of no-failure operation. Modeling of failures were carried out by mean of division of investigated system into two in-series connected subsystems, one of them indicated independent failures, but the other indicated common failures. Due to joined modeling of single and common failures resulting intensity of failures is the amount incompatible components: intensity statistically independent failures and intensity of common failures of elements and system in total.It is shown the influence of common failures of elements on average time of no-failure operation of system. There is built the scale of preference of systems according to criterion of  average time maximum of no-failure operation, depending on portion of common failures. It is noticed that such common failures don’t influence on the scale of preference, but  change intervals of time, determining the moments of systems failures and excepting them from the number of comparators. There were discussed two problems  of conditionally optimization of  systems’  reservation choice, taking into account their reliability and cost. The first problem is solved due to criterion of minimum cost of system providing mean probability of no-failure operation, the second problem is solved due to criterion of maximum of mean probability of no-failure operation with cost limitation of system.